2016
DOI: 10.4102/phcfm.v8i1.1184
|View full text |Cite
|
Sign up to set email alerts
|

How to change organisational culture: Action research in a South African public sector primary care facility

Abstract: BackgroundOrganisational culture is a key factor in both patient and staff experience of the healthcare services. Patient satisfaction, staff engagement and performance are related to this experience. The department of health in the Western Cape espouses a values-based culture characterised by caring, competence, accountability, integrity, responsiveness and respect. However, transformation of the existing culture is required to achieve this vision.AimTo explore how to transform the organisational culture in l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 4 publications
(6 reference statements)
0
8
0
Order By: Relevance
“…The culture moved towards greater communication, appreciation, accountability, teamwork, and patient orientation among other positive changes. Importantly, the study showed that organisational transformation is possible even in the context of resource constraints and heavy workloads [89].…”
Section: Part B: Responses To Organisational Challengesmentioning
confidence: 89%
“…The culture moved towards greater communication, appreciation, accountability, teamwork, and patient orientation among other positive changes. Importantly, the study showed that organisational transformation is possible even in the context of resource constraints and heavy workloads [89].…”
Section: Part B: Responses To Organisational Challengesmentioning
confidence: 89%
“…55 There are several studies showing how it can be changed, although these have not been linked to propensity for innovation per se. 56…”
Section: Theories and Conceptsmentioning
confidence: 99%
“…There is also potential for deploying Barrett's framework in a survey-based research design, following Ludolf, Silva, Gomes and Oliveira [39]. From a different methodological perspective, further research could also follow Mash, De Sa and Christodoulou [25], who advocate participatory action research with the management team over an extended period of time, to evaluate the effect of various interventions on the sustainability culture of the organisation. Whether qualitative or quantitative approaches are used, a baseline assessment prior to any interventions would be desirable.…”
Section: Conclusion and Further Workmentioning
confidence: 99%
“…Moreover, Barrett's framework in particular has, to our knowledge, not been assessed for its operational value vis a vis sustainability. Typical studies on values alignment usually relate to general values and to the achievement of general business goals, rather than being more specific to ambitions of an organisation becoming a global sustaining organisation (e.g., [25]).…”
Section: Introductionmentioning
confidence: 99%